A STUDY TO ASSESS THE DISTRIBUTION OF SUSPECTED ADVERSE EVENTS FOLLOWING IMMUNISATION REPORTED IN A METROPOLITAN CITY IN INDIA - Sophie Simon; Shalini Rawat; Rohan Sangam; G D Velhal (Global Journal of Public Health Medicine)
Introduction: Adverse Events Following Immunization (AEFI) may be considered as major setback to